Comparison of Intraosseous and Conventional Dental Anesthesia in Children—A Scoping Review - Anastasia Dermata; Sotiria Davidopoulou; Aristidis Arhakis; Nikolaos Dabarakis; Konstantinos N. Arapostathis; Sotirios Kalfas (Dentistry Journal, 2025)
Background/Objectives: The main purpose of the present scoping review was to map and explore the efficacy of computer-controlled intraosseous anesthesia (CCIA) in comparison with conventional dental anesthesia in pediatric dental patients. Secondarily, this study aimed to compare the acceptance and preference factors between CCIA and conventional dental anesthesia in children. Given the limited and heterogeneous nature of the available literature, this review aimed to identify gaps and scope the extent of research conducted in this area, providing a foundation for future, more targeted studies. Methods: The search was conducted in 19 electronic databases, and the appropriate studies were identified according to PRISMA-ScR guidelines. Only split-mouth randomized controlled clinical trials that reported on the clinical outcomes of CCIA in children were included. Two reviewers worked independently on the screening and selection of the studies. The same two reviewers carried out the data extraction and the risk of bias assessment, using the Cochrane risk of bias tool. Due to the exploratory nature, this review focused on mapping the characteristics, outcomes, and research trends rather than synthesizing effect sizes. Results: Out of 841 papers, 2 randomized clinical trials were ultimately included in the scoping review. The outcomes were categorized as primary (including results that answered the focus question) and secondary (relating to additional quality characteristics). Regarding the primary outcomes, in both studies, intraosseous anesthesia was efficacious in achieving the adequate level of anesthesia. One of the secondary outcomes was the acceptance and preference of CCIA in comparison with conventional dental anesthesia in children. The limited number and the high risk of bias in existing studies highlight the necessity for more comprehensive and high-quality research. Conclusions: The selected studies support the assertion that CCIA is a promising technique since it results in less pain perception and is preferred by patients compared to conventional local anesthesia. However, the existing literature is limited and at high risk of bias. Thus, further targeted investigations are needed to evaluate and yield more definitive results regarding the superiority of CCIA.